(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Under British administration, modern Indian education began. As people educated in India inHindu and Muslim institutions were not up to the task of the British government, Lord Macaulay, in his actof February 8, 1935, put forward a proposal for a Western-oriented educational system in India. It placedpopular science at the top of European literature and science, a strategy that has lasted to this day.Western influence also has positive aspects. This triggered a revival and revival of Indian educationalideas. Many educated Western intellectuals developed an appreciation for their culture and civilizationand wished to adapt Western approaches to education to Indian ideals and circumstances. The presentstudy is of great importance in the field of the history of Indian education and for students of education,policymakers, social thinkers, educators, teachers, administrators, and all other interested parties. It wasfound that the Indian government has brought together many public authority advisory groups,commissions, agreements and initiatives to promote and further the overall educational situation of thecountry.